Detention of a person committed a criminal offence: criminal procedural and forensic characteristics - V. G. Drozd (Bulletin of Kharkiv National University of Internal Affairs)
The features of detention of a person who has committed a criminal offence are analysed. The main features of the legal nature of the relevant institution in the system of pre-trial investigation of criminal offences are presented, and also the idea of the main range of problematic issues arising in the course of implementation of the relevant provisions of law is summarised. The author provides arguments on the procedural grounds for applying detention of a person committed a criminal offence, and also outlines the main forensic (general and special) features of its implementation.